PRINCIPALS’ MANAGEMENT STRATEGIES AS CORRELATES OF TEACHERS’ COMMITMENT TO WORK IN PUBLIC SECONDARY SCHOOLS IN ANAMBRA STATE - Muoto, Rose C.; Chukwudolue , Anuli Chinelo; Obi , Ngozi Chinyere (Int'l Journal of Education Research and Scientific Development, 2024)
The study examined principals’ management strategies as correlates of teachers’ commitment to work in public secondary schools in Anambra State. Two research questions guided the study and two null hypotheses were tested at .05 level significance. The study adopted correlational research design. The population of the study comprised 5396 (5,133 teachers and 263 principals) in 263 public secondary schools in six Education Zones in Anambra State. A sample of 579 respondents (513 teachers and 66 principals) was drawn using proportionate stratified and simple random sampling technique. The instruments for data collection were a researchers-structured questionnaire titled: “Principals’ Management Strategies Questionnaire (PMSQ), and Teachers’ Commitment to Work Questionnaire (TCWQ)”. The face and construct validity of the instruments were established by three experts; one from Measurement and Evaluation and two in Educational Management. The reliability of the instruments was determined using Cronbach Alpha Coefficient method which gave coefficient values of 0.86, 0.82 and 0.86 respectively. Pearson Product Moment Correlation Coefficient was used to answer the research questions and test the hypotheses at 0.05 level of significance. The study revealed that principals’ instructional leadership strategy (r = 0. 676; p < 0.000), and principals’ decision-making strategy (r = 0. 683; p < 0.000) positively and significantly relate to teachers’ commitment to work in public secondary schools in Anambra State. The study recommended that school administrators should continue to promote participatory decision-making processes in their schools by involving teachers in decision-making so as to increase the level of morale and motivation among teachers.